1988
DOI: 10.3109/00365528809090188
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Candidosis in Progressive Systemic Sclerosis: Occurrence, Significance, and Treatment with Fluconazole

Abstract: Esophageal mucosal brushings from 51 consecutive patients with progressive systemic sclerosis (PSS) (group I), 18 PSS patients continuously treated with high-dose ranitidine or omeprazole (group II), 34 controls referred to the outpatient clinic for endoscopy (group III), and 10 patients receiving long-term potent antireflux therapy for idiopathic gastroesophageal reflux (group IV) were cultured for Candida albicans. There were 44%, 89%, 9%, and 0% Candida albicans culture-positive patients in groups I through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 11 publications
2
26
1
1
Order By: Relevance
“…TGase-mediated cross-linking of germ tubes to epithelial cells may also impede the dislodging of fungi and epithelial cells from surface mucosa by the mechanical actions associated with eating and swallowing. The importance of esophageal motility in resisting candidal invasion is supported by evidence that smooth-muscle atrophy leading to impaired esophageal peristalsis is a risk factor for esophageal candidiasis [20]. Easier removal of hwp1/hwp1 hyphae from the keratin layer of the esophageal epithelium or reduced frequency of establishment of an infected locus within the esophagus could lessen the fungal burden to a level that host defenses could manage.…”
Section: Discussionmentioning
confidence: 97%
“…TGase-mediated cross-linking of germ tubes to epithelial cells may also impede the dislodging of fungi and epithelial cells from surface mucosa by the mechanical actions associated with eating and swallowing. The importance of esophageal motility in resisting candidal invasion is supported by evidence that smooth-muscle atrophy leading to impaired esophageal peristalsis is a risk factor for esophageal candidiasis [20]. Easier removal of hwp1/hwp1 hyphae from the keratin layer of the esophageal epithelium or reduced frequency of establishment of an infected locus within the esophagus could lessen the fungal burden to a level that host defenses could manage.…”
Section: Discussionmentioning
confidence: 97%
“…Strictures are probably more prevalent, more difficult to treat, and more symptomatic (due to associated dysmotility) in PSS than non-PSS reflux patients although there has not been any direct comparisons between the 2 patient groups. Candida esophagitis is common in PSS but not in non-PSS reflux patients [79][80][81] and treatment may reduce dysphagia.…”
Section: Diagnosis and Treatment Of Esophageal Dysfunction In Pssmentioning
confidence: 99%
“…It is well known that endoscopic biopsy can detect a malignant degeneration in Barrett's esophagus in 89.1% of cases. The incidence of Candida esophagitis is significantly increased during treatment with H2-antagonists, in scleroderma [24], and in the acquired immunodeficiency syndrome [25]. Therefore, it has been suggested that annual endoscopy and biopsy of patients with Barrett's esophagus are justified [19,20].…”
Section: Tumofsmentioning
confidence: 99%